The Development of the Learning Management Process for Inculcating 12 Principal Values with the Idea of Sustainable Learning for Secondary Schools - Sutthiporn Boonsong, Thosporn Sangsawang, Kasina Chinsri (International Journal of Advanced Science and Technology, 2020)
Thai education has a policy to develop good values of Thai people with 12 values. Government have expected secondary school teachers to be able to use the learning management process to develop their students to have good values. The purpose of this research was to develop and study the results of the implementation of the Learning Management Process for Inculcating 12 Principal Values with the Idea of Sustainable Learning Concepts for Secondary Schools. The samples were composed of academicians, experts, administrators, teachers and students from six regions of Thailand in the academic year 2017 – 2018. The study design used the research and development methodology with the integration of survey research, experimental research. The results of this research were: 1) learning process developed has 11 plans, experimental results and learning development of grade 8 students found that teachers can use learning management in planning and students are satisfied in the learning process, 2) management process were to develop the testing efficiency of the leaning process, 3) assessment of testing the efficiency showed learning levels were high overall in various aspects, including use information technology, nature of flexible learning content, in terms of efficacy, creativity, morality and ethics, and teaching that focuses on the learning process; analytical thinking, group processes, process skills, and adoption in developing better features for all sexes, ages, and class levels of learners.